Autoimmune Thyroid Diseases and Thyroid Cancer in Pemphigus: A Big Data Analysis - Kridin, Khalaf; Khamaisi, Mogher; Comaneshter, Doron; Batat, Erez; Cohen, Arnon D. (Frontiers in Medicine, 2018)
There is a little consensus regarding the association of pemphigus with autoimmune thyroid diseases. While this association had been confirmed by some observational studies, others had refuted it. We aimed to study the association between pemphigus and Hashimoto's thyroiditis, Grave's disease, and thyroid cancer using a large-scale real-life computerized database. A cross-sectional study was performed to compare pemphigus patients with age-, sex-, and ethnicity-matched control subjects regarding the prevalence of overt thyroid diseases. Chi-square and t-tests were used for univariate analysis, and a logistic regression model was used for multivariate analysis. The study was performed using the computerized database of Clalit Healthcare Services ensuring 4.5 million individuals. A total of 1,985 pemphigus patients and 9,874 controls were included in the study. The prevalence of Hashimoto's thyroiditis (12.9 vs. 11.9%; P = 0.228), Graves's disease (0.7 vs. 0.7%; P = 0.986), and thyroid cancer (0.7 vs. 0.5%; P = 0.305) were comparable among patients with pemphigus and control subjects. In sex-stratified analysis, pemphigus associated significantly with Hashimoto's thyroiditis among male patients (OR, 1.36; 95% CI, 1.04–1.79). In multivariate analysis adjusting for potential confounding factors, no independent associations between the conditions were revealed. Study findings were robust to sensitivity analysis that included only patients under pemphigus-specific treatments. In conclusion, Hashimoto's thyroiditis was found to be associated with pemphigus only among male patients, but not among all patients. Physicians treating patients with pemphigus might be aware of this possible association. This study does not provide a clue for an association of pemphigus with Grave‘s disease or thyroid cancer.